Looking for Information: An Exploratory Analysis to Explain Public Information-Seeking Behaviors About Mosquito Control - Shelli D Rampold; Melissa Cater; Ricky W Telg (Journal of Applied Communications, 2020)
Mosquitoes pose substantial risks in communities worldwide, and the extent and type of such risk may vary across communities and regions. The integrated mosquito management approach integrates multidisciplinary methods into practical strategies tailored to local communities. Reduction of mosquito larval sources via community engagement in at-home mosquito control behaviors is a key component of this approach. Best methods of communicating information to the public to foster knowledge and motivation to engage in local mosquito control efforts. The purpose of this descriptional, correlational study was to describe the Florida public’s mosquito control information search behaviors, as well as examine factors that may explain those behaviors. Findings revealed statistically significant relationships existed between respondents’ information search frequency and their subjective and objective knowledge, importance of mosquito control, personal responsibility, income and education. Significant relationships were also observed between personal responsibility and homeownership and type of residence. Respondents perceived CDC websites and Florida DOH websites as the most trustworthy of the sources listed, and were most likely to use local mosquito control program websites when searching information. Local mosquito control districts should use the findings of this study to target passive audiences and facilitate their future engagement in mosquito control dialogues. Future research is needed to further examine the directionality and predictive nature of variables examined in this study.
Keywords: Florida residents; information-seeking behaviors; mosquito control; science communication; personal responsibility